Effect of Index of Conciousness (Ioc2) Monitoring on Remifentanil Dosage During Desflurane Anesthsia: A Randomized Trial - Mahaseth, Nirajan; Khapung, Rabin; BS, Budal (Journal of Karnali Academy of Health Sciences, 2019)
Background: Our study investigated the effects of IOC2 index monitoring on remifentanil dosage during desflurane anesthesia. The objective of this study was to compare the intra-operative events and recovery characteristics between remifentanil adjusted by IOC2 monitoring guidelines versus remifentanil adjusted by clinical experience according to fluctuation in blood pressure and heart rate during desflurane anesthesia. Methods: Total of 50 consecutive patients of American Society of Anesthesiologists (ASA) status I and II, aged 18-65 years, BMI 18-30 kg/m2 undergoing elective laparoscopic cholecystectomy under desflurane anesthesia were enrolled. The patients were randomized and allocated into 2 groups, group T (Trial group=25) and group C (control group=25) using sealed envelope method. The infusion rate of remifentanil was adjusted according to IOC2 monitoring guideline between 30 to 50 in Group T whereas the infusion rate of remifentanil is adjusted by clinical experience according to fluctuation in blood pressure in group C. Remifentanil dose, adjustment frequency, infusion duration, intraoperative events, and quality of anesthetic recovery were compared between the two groups. Results: Mean dose as well as the adjustment frequency of remifentanil was significantly higher in group T in compared with group C (0.1376±0.0268 vs 0.0956±0.0223 mcg/kg/min and 5.19±1.97vs1.7±0.57 times/surgery, P<0.05). IOC2 value at the time of skin incision, at the time of gall bladder resection and at the time of skin suture was significantly different between two groups (all P value <0.05). Although apparent differences in frequencies of hypotension, bradycardia, hypertension, the total number of patents with intraoperative events were not statistically different between two groups (all P > 0.05). Both groups had similar voluntary eye opening time, extubation time, emergence agitation ,residual sedation 1 and 10 minutes after extubation, post-operative vomiting and NRS score (in PACU and 24 hours after extubation (all P > 0.05). Conclusion: IOC2 data was significantly high when opioid adjusted by clinical experience. The dose of opioid used according to IOC2 (30-50) monitoring guideline utilized higher dose in compared with dose used by clinical experience however, the intraoperative hemodynamic and recovery characteristics was unchanged. Hence, application of IOC2 monitoring might be beneficial to adjust the analgesic depth.